Tramas tróficas de peces de arrecifes en la región noroccidental de Cuba.I. Contenido estomacal - Hernández, Ivet (2008)
Studies on the reef fishes of Cuba are not rare, but most have two basic limitations: small sample sizes and exclusion of small species. Our study sampled more species and larger samples in the sublitoral region of Havana city (23º7.587 ́ N, 82º25.793 ́ W), 2-18 m deep. We collected fish weekly from October 2004 through February 2006 with traps and harpoon. Overfishing has modified the fish communities. We used the relative importance index to describe the diets of carnivore and omnivore species, and a modification of the relative abundance method for the herbivores and sponge-eating species. The main food items are benthonic crustaceans (crabs, shrimp, copepods) and bony fish (mainly demersal species). Most species are eurifagous and thus, less affected by anthropic disturbance than specialist feeders.